Integration of Multicultural Values in Project-Based Learning: A Case Study on the Batik and Textile Creative Craft Program - Iswanto, Iswanto; Ma’ruf, Ahmad; Sholikhudin, M. Anang (ISLAMIKA, 2025)
This study investigates the integration of multicultural values into project-based learning within the Batik and Textile Creative Craft program at Vocational High School 1 Jabon Sidoarjo, in response to the growing need for character education in ethnically diverse vocational settings. While technical competence remains a central focus of vocational education, the absence of systematic efforts to instill cultural values has limited students’ development in areas such as tolerance, inclusion, and social awareness. Using a qualitative descriptive approach, data were collected through semi-structured interviews, classroom observations, and document analysis involving school leaders, teachers, students, and community figures. Data analysis employed source triangulation and followed a process of data reduction, presentation, and verification to ensure validity. The findings demonstrate that project-based learning effectively serves as a pedagogical medium for embedding multicultural values, particularly through collaborative activities rooted in the culturally significant practices of batik and textile craftsmanship. Students developed heightened awareness of diversity and demonstrated improved inclusive and cooperative behaviors. The integration of multicultural principles was facilitated by the alignment between the curriculum and the local cultural context, which supported the internalization of values in an experiential and meaningful manner. This study concludes that the synergy between technical training and multicultural education through project-based learning can contribute significantly to the development of inclusive vocational education. The findings offer practical insights for other vocational institutions seeking to advance character education through culturally responsive pedagogies.